Transformation of Malaysia’s Higher Education System: Malaysia Education blueprint (2015-2025) - Ganapathy, Malini (National Higher Education Research Institute, Universiti Sains Malaysia, 2016)
Globalisation and technology have completely transformed sectors such as finance, services and telecommunications and the higher education sector will likely face the same transformation or as a matter of fact is already experiencing disruption from new models such as Massive Open Online Courses (MOOCs).